O consumo sustentável em food trucks e a responsabilidade civil do microempreendedor individual à luz do CDC - Barros, Anne Caroline Rodrigues (2019)
The present research deals with the viability of the adaptation of the economic development to the activities of microfoods traveling by food trucks, aiming at the application of the concept of sustainability in all stages of production and supply of goods and services, to the sustainable consumption of its final recipient. It is conceived that the implementation of sustainability in the scope of consumption and the application of the civil responsibility of the suppliers of goods and services are fundamental for the maintenance of a balanced environment, with the aim of guaranteeing a healthy human subsistence. In the light of these elucidations, it may be conceived, in turn, that not only are companies responsible for promoting the neutralization of negative externalities, but the act of consumption is also a stimulant factor of economic market activities, and the consumer, in turn , a subject of rights and duties, who acts as a promoter of environmental sustainability with a view to its protection, that is vital for its existence and postponement. In view of this, it is necessary to analyze the adequacy of the activities carried out by these entrepreneurs, who, in a mass and abrupt manner, were inserted in the economic market, especially those developed by individual micro-entrepreneurs of food trucks. These should also be submitted to the analysis of the promotion of sustainable development in their activities, together with their consuming public and final recipients, who become aware of sustainable consumption. In order to develop the theoretical reference of the dissertation, the scientific method employed was the deductive and as technical procedures, historical and bibliographical procedures were used, given that, in order to substantiate the theme, we explored books, scientific articles, websites, periodicals, jurisprudence, in addition to the doctrinal teachings of several authors who have already studied the subject. Finally, the exploratory research was carried out directly in the Public Organisms responsible for supervising the microenterprise activities of food trucks in the municipalities of João Pessoa and Cabedelo, Paraíba.